Determination of preclinical safety of oil obtained from Pachira aquatica Aublet (Malvaceae) seeds: histopathological, biochemical, hematological, and genetic toxicity studies in rats. - Marcelino, J.M.; Villas Boas, G.R.; Cunha, M.; Deus Júnior, R.; Castro, L.H.; Araújo, F.H.; Traesel, G.K.; Dos Santos, A.C.; Souza, R.I.; Paes, M.; Gubert, P.; Guterres, Z.D.R.; et al. (Drug and Chemical Toxicology, 2022)
Pachira aquatica is a species used for medicinal and food purposes and has numerous phytochemicals that may have systemic toxic effects and damage to genetic material. This study aimed to evaluate acute and short-term oral toxicity, as well as genotoxic and clastogenic effects of oil extracted from P. aquatica (PASO) seeds in rats and Drosophila melanogaster. The results obtained with biochemical and hematological analyses did not show significant changes in any evaluated parameters when compared with reference values for the species used in the study. Data from the histopathological analysis corroborated results found in this study. These findings indicate low acute and short-term toxicity following oral PASO exposure in rats under the experimental conditions tested. Tests performed in rats showed that PASO did not present significant genotoxic or clastogenic effects on the cells analyzed with the three doses tested. Treatment with PASO in the offspring of HB crossing, which showed high cytochrome P450 levels, did not exhibit genotoxic activity, as demonstrated by the SMART test. These results suggest that products from the hepatic oil metabolism did not show genotoxicity under the conditions tested. Together, the results indicate that, under the experimental conditions tested, PASO is safe for repeated intake. As PASO exhibited low potential to cause harmful effects on living organisms, our study encourages further research aimed at assessing its pharmacological activity, since it is a widely consumed plant.